The Experiential Analysis of Opinion Column Section Media Texts about Sexual Harrasment in Jakarta Post: A Systemic Fuctional Analysis - Situmorang, Maria Clara Timorina; Rangkuti, Rahmadyah; Perangin-Angin, Alemina (Journal of Languages and Language Teaching, 2025)
This study adopts an experiential analysis approach to examine how sexual harassment is represented in opinion columns published by The Jakarta Post. Utilizing Halliday’s Systemic Functional Linguistics (SFL) as the theoretical framework, the research focuses on exploring how language is structured to convey experiential meaning, particularly through the transitivity system. As a form of qualitative and descriptive research, this study investigates online news texts with the aim of uncovering how linguistic choices reflect and construct social realities. The central analytical focus lies in identifying types of processes, participant roles, and circumstantial elements within the clauses of the texts. These components are crucial for understanding how actions, events, and relationships are framed in relation to gender and power dynamics. Through the analysis of 436 clauses, the findings indicate that material and relational processes are the most frequently used. Material processes reflect actions and events, while relational processes emphasize classification, attribution, and identification. Their prevalence suggests that opinion columnists highlight both the concrete experiences of harassment and the ways individuals and groups are labeled or characterized. This dominance illustrates how language is strategically employed to both narrate and evaluate incidents of sexual harassment. By analyzing these linguistic features, the study sheds light on how media discourse contributes to shaping public understanding and societal attitudes toward gender-related issues. Ultimately, the study provides valuable insight into how opinion columns, as influential media texts, can reinforce or challenge dominant ideologies, thus playing a critical role in public discourse surrounding sexual harassment.